The Values Developed In Shaping The Religious Character of the Kuta Traditional Community in Ciamis Regency - Darisman, Dede; Nurdin, Encep Syarief; Kosasih, Aceng; Nurbayani K, Siti (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
The objectives of this study are: 1) To identify the religious values that develop in the traditional and social life of the Kuta Indigenous community in Ciamis Regency, 2) To analyze the mechanisms of development and inheritance of religious values, and 3) To explain the contribution of these religious values to the formation of the religious character of the Kuta Indigenous community. A qualitative phenomenological approach was applied in this study, using observation, interviews, and documentation reviews as data collection techniques. The analysis process was carried out descriptively-analytically to trace how these values developed in forming the religious character of the Kuta Indigenous community in Ciamis Regency. The results of the study indicate that: 1) The religious values of the Kuta Indigenous community include monotheism, togetherness and mutual cooperation, adherence to taboos and customs, simplicity, and ecological ethics. These values become the spiritual and social foundations that shape the community's lifestyle. 2) The mechanisms of development and inheritance of values. Religious values are developed through traditional rituals, religious activities, social practices such as cooperation and joint deliberation, as well as customary rules that regulate behavior and village spatial planning. The process of inheritance occurs between generations through the internalization of culture, customary authority, and collective participation. 3) These values shape the religious character of the community in four dimensions: spiritual (ancestral reverence and sacred rituals), social (solidarity and cohesion through collective cooperation), moral (discipline and obedience through taboos and customs), and ecological (environmental concern through customary prohibitions and protection of sacred forests).